A Systematic Review of Public Housing, Poverty (De)Concentration, and Risk Behaviors: What About Youth?. (January 2022) - Kim, Bitna; Merlo, Alida V.; Park, Junhwi; Hong, Young-Oh
Mobility housing programs aim to deconcentrate poverty in public housing areas. Previous synthesis research results describe the potential negative impact of mobility programs on the physical and mental health of youth. The current systematic review aims to expand our knowledge of the effects of living in a public housing development and leaving public housing and moving to a new neighborhood on youth risk behaviors, including both general crime/delinquency and substance use, sexual risk behavior, behavioral problems, and binge drinking. The systematic review process produced 7 primary research studies on public housing effects and 10 research studies on resettlement effects. Regarding public housing effects, five studies found a higher incidence of youth risk behaviors in public housing areas, while two studies concluded that not all children and adolescents living in public housing areas are adversely affected by the local environment. Of the 10 studies on the effects of relocation from public housing to other areas, 2 non-randomized controlled trial (RCT) studies found negative impacts, but 8 RCT studies found diversity in relocation effects on youth risk behaviors. These results highlight the need for tailored services for relocated youth taking into consideration their gender, age, family characteristics, and relocation sites. No studies on diversification housing projects satisfied the inclusion criteria in the current systematic review. With a thorough examination of the literature and a discussion of implications, a clear path for future inquiry and youth interventions is presented.